2018
DOI: 10.1002/aoc.4408
|View full text |Cite
|
Sign up to set email alerts
|

Selective oxidation of ethylbenzene to acetophenone over Cr(III) Schiff base complex intercalated into layered double hydroxide

Abstract: A new heterogeneous catalyst, Cr(III) Schiff base‐containing layered double hydroxide, was synthesized using the intercalation method. The Cr(III) Schiff base complex derived from 2‐hydroxy‐1‐naphthaldehyde and 4‐aminobenzoic acid was intercalated into the layered double hydroxide. The synthesized materials were characterized using inductively coupled plasma atomic emission spectrometry, energy‐dispersive X‐ray analysis, scanning electron microscopy, X‐ray diffraction, Brunauer–Emmett–Teller surface area measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…One of the most often used anionexchange families is the layered double hydroxides (LDHs) in which the positive charges of the double (M 2+ and M 3+ ) metal hydroxide layers were compensated by interlamellar solvated anions. 20,21 These interlayer anions can be further exchanged with more or less difficulties by different type of anions such as amino carboxylates, 22,23 polyoxometallates, 24 Schiff-base complexes, 25 polymeric anions, 26 DNA, 27 etc. In parallel to this process, surface adsorption of the guest molecules could also occur.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most often used anionexchange families is the layered double hydroxides (LDHs) in which the positive charges of the double (M 2+ and M 3+ ) metal hydroxide layers were compensated by interlamellar solvated anions. 20,21 These interlayer anions can be further exchanged with more or less difficulties by different type of anions such as amino carboxylates, 22,23 polyoxometallates, 24 Schiff-base complexes, 25 polymeric anions, 26 DNA, 27 etc. In parallel to this process, surface adsorption of the guest molecules could also occur.…”
Section: Introductionmentioning
confidence: 99%
“…immobilized metalloporphyrins and their catalysis systems [31][32][33][34][35] adapting to the cleaner production process. However, the resulting yields (acetophenone and phenylethanol (ONE + OL), less than 25%) were lower than those obtained from the catalytic systems above [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] . In addition, RSM was also seldom used in the catalytic field of metalloporphyrins [14][15][16][17]19,20,[31][32][33][34][35] .…”
mentioning
confidence: 74%
“…It was found that the conversion of toluene in the presence of solvents was decreased due to the blocking of active sites by solvent molecules or that there could be a diffusion rivalry between solvent and substrate molecules for active sites. [33]…”
Section: Effect Of Various Solventsmentioning
confidence: 99%
“…[30] We have previously studied heterogeneous oxidation catalysts for aromatic hydrocarbons assisted by transition metal. [31][32][33][34] Mn(III) and Fe(III) Schiff base complexes supported on layered double hydroxide have been recently tested for the oxidation of toluene. [35] The present study will focus on the catalytic oxidation of toluene over LDH-supported heterogeneous catalysts, LDH-[NAPABA-M] {where M = Cu(II), and Co(II)} with tert-butyl hydroperoxide as an oxidant under solvent-free conditions.…”
Section: Introductionmentioning
confidence: 99%